261 Increasing dietary amylose reduces rate of starch digestion and increases microbial fermentation in weaned pigs - Tan, F P Y (J Anim Sci, 2020)
Beneficial effects of SCFA in modulating gut health stimulated interest on dietary strategies to increase intestinal microbial activity and digesta SCFA. Amylose has lower apparent ileal digestibility (AID) than amylopectin. In the large intestine, undigested starch is fermented by microbes producing SCFA. The objective was to determine effects of increasing dietary amylose on starch flow and metabolite profile along the intestinal tract in weaned pigs. Weaned pigs (n=32; initial BW, 8.4 kg) were randomly allocated to 4 diets containing 67% starch with 0, 20, 35, or 70% amylose in a randomized complete block design. On day 21, pigs were euthanized to collect digesta and feces for evaluating starch digestion and metabolite profiles. Apparent hindgut fermentation (AHF) was calculated as apparent total tract digestibility minus AID. Feed intake was 12% lower (P < 0.05) and growth rate was 18% lower (P < 0.05) for pigs fed 70% amylose than pigs fed 0, 20, or 35% amylose. Feed efficiency was greatest (P < 0.05) for pigs fed with 35% amylose. The AID of starch was 44% lower (P < 0.05) in pigs fed 70% amylose. Starch was completely digested by the proximal colon in pigs fed 0, 20, or 35% amylose, but AHF of starch was 14% greater (P < 0.05) in pigs fed 70% amylose. Increasing dietary amylose did not alter digesta SCFA in the small intestine, but increased (P < 0.05) digesta SCFA in the cecum, specifically acetate and total SCFA, and increased (P < 0.05) propionate and valerate in all sections of the colon. In conclusion, increasing dietary amylose in weaned pigs stimulated hindgut fermentation of starch with a corresponding increase in digesta total SCFA in the cecum and colon. Optimizing dietary amylose may exert its effect as dietary prebiotic while promoting an optimal growth rate in young pigs.